Online dispute resolution for small claims: is this the only realistic solution? - Nieva-Fenoll, Jordi (Revista Ítalo-Española de Derecho Procesal, 2022)
Some jurists believe that the judicial process is not adequate for these lawsuits when they are transnational, but in fact, neither is it when they are national. It is true that a transnational claim is challenging in terms of applicable law, the search for national lawyers, the search of evidence and even the translations. But actually all inconveniences are based upon a very old mentality linked with the also very old ‘de minimis non curat praetor’. Whoever thinks that dealing with transnational small claims is not really feasible, does not see how to deal with them adequately in domestic law either. These authors also think that the resolution of small claims should be transferred to mediation –often useless–, to consumer arbitration, whose institutional development as parallel to state justice is extremely complicated, or even to collective redress, although in the vast majority of cases there is not really a group of stakeholders that can be managed together. Furthermore, organizing this kind of collective redress is very difficult. It’s maybe necessary to remember that class-actions in the US almost never reach the trial phase.